1992
DOI: 10.1002/art.1780350413
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma arthritidis mitogen. Vβ engaged in mice, rats, and humans, and requirement of HLA‐DRα for presentation

Abstract: Objective. Mycoplasma arthritidis mitogen (MAM) is mitogenic for mouse, rat, and human T cells, and behaves as a superantigen in mice through its capacity to bind to the (Y chain of I-E molecules and engage entire sets of T cells expressing specific Vp. Here, we have attempted to fully characterize the V,-engaging activities of MAM in mice, and define similar activities in rats and humans.Methods. Multiprobe RNase-protection assays and mice transgenic for human DRcu, DRP, and DRaP were utilized for this pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 49 publications
4
24
1
Order By: Relevance
“…Results from competitive binding assays also reveal cross-inhibition between TSST-1, which is known to span the peptide groove, and MAMwt (38). MAM dimers presented to T cells interact with human V␤ regions 19.1 (alternatively termed V␤ 17.1), 3.1, 11.1, 12.1, and V␤ 13.1 in vitro (61). However, MAM also interacts with the T cell complementary determination region 3, indicating that, while an appropriate V␤ region is present on a TCR, MAM may not activate the T cell unless appropriately stabilized through an interaction with complementary determination region 3 (15).…”
Section: Substitution Of His-14 and Asp-31 For Alanine Significantly mentioning
confidence: 93%
“…Results from competitive binding assays also reveal cross-inhibition between TSST-1, which is known to span the peptide groove, and MAMwt (38). MAM dimers presented to T cells interact with human V␤ regions 19.1 (alternatively termed V␤ 17.1), 3.1, 11.1, 12.1, and V␤ 13.1 in vitro (61). However, MAM also interacts with the T cell complementary determination region 3, indicating that, while an appropriate V␤ region is present on a TCR, MAM may not activate the T cell unless appropriately stabilized through an interaction with complementary determination region 3 (15).…”
Section: Substitution Of His-14 and Asp-31 For Alanine Significantly mentioning
confidence: 93%
“…It is well established that MAM, like other Sags, bind to MHC class II molecules on APCs and is presented as such to T cells by interacting with their TCR, and more specifically with the region Vb 3.1, 13.1, 14, and 17 in humans and Vb 6, 8.1, and 5.1 in mice (38). MAM induces different Vb repertoires depending on the HLA-DR haplotype, which indicates that the Vb specificity of MAM is determined by the MAM/HLA-DR complex (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Antibody against MAM has also been detected in sera from patients with rheumatic diseases (39). The major T-cell subset identified in the synovium of several human rheumatoid arthritis patients expressed the exact V ␤ that has been found to be responsive to MAM (1,32). It has also been demonstrated that MAM can stimulate human T-cell proliferation (2), promote human B-cell differentiation (24), and upregulate human NK cell activity (26).…”
Section: Discussionmentioning
confidence: 99%